Replacement migration and changing preferences: immigrant workers in cleaning and domestic service in Portugal - Pereira, Sónia (2013)
This paper analyses processes of replacement faced by immigrant workers in the labour market by looking at the two most relevant economic activities for the integration of immigrant women: cleaning and domestic service. For most of its immigration history, Portugal relied on immigrants from Lusophone African (PALOP) countries*mostly from Cape Verde*to supply the workforce necessary to complement native workers in these activities. However, as the immigration scenario changed at the end of the 1990s with the arrival of Eastern European and Brazilian women, so did the hiring options available to employers. At the same time, immigration from PALOP countries underwent a consolidation process, with implications for the immigrants’ own working preferences and integration processes. The objective of this paper is to address the changes that occurred in the integration of immigrant workers in these two low-skilled activities between 1998 and 2006 and in the light of both employers’ and workers’ preferences and their respective labour market strategies. The underlying hypothesis is that the prevailing working conditions in each of these activities condition both employers’ and workers’ preferences and their implementation, thereby producing different outcomes in terms of processes of replacement migration and the substitution of workers.